The Role of Social Support in the Anxiety and Depression of Elderly - Fardin Alipour; Homeyra Sajadi; Ameneh Forouzan; Hamid Nabavi; Esmaeil Khedmati (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: This study has been conducted to investigate the «social support» various roles in anxiety and depression of elderly people, in Tehran’s second district habitants. Methods & Materials: The method of study is causal-comparative and required data was collected by Norbeck Social SupportQuestionnaire and Anxiety and Depression Scale. The sample includes 100 elder subjects who are 60 years old and over which having been chosen from elderly population of Tehran’s second district. Regression and correlation coefficient tests have been applied for dataanalysis. Results: Findings show that anxiety and depression rates were 44% and 40% respectively in elder subjects. Correlation test showed that all types of social support pecuniary, emotional, functional, structural support) had a reverse and significant relationship with depression and anxiety. The results of multiple regression showed that pecuniary and structural support were significant predictive for anxiety and pecuniarysupport was significant predictive for depression in elderly peopel. Conclusion: The Results of this study emphasize on the importance of social determinants of health role, especially, social support on the mental disorders of the elderly. Taking this inexpensive resource into account in tackling elderly depression and anxiety, and as a result,improvement of their quality of life, is of a great importance.